1996
DOI: 10.3109/00365529609006776
|View full text |Cite
|
Sign up to set email alerts
|

Giant Splenic Cyst with High Serum Concentration of CA 19-9 Failure of Treatment with Percutaneous Transcatheter Drainage and Injection of Tetracycline

Abstract: The accumulation of cystic fluid in splenic epithelial cysts may be attributable not only to the secretion of the lining cells but also to influx from the splenic sinuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…Cysts derived from the accessory spleen are very rare, with all reported cases located in the pancreas . No intraabdominal cyst derived from the accessory spleen in the greater omentum, similar to our case, has been reported in the literature.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Cysts derived from the accessory spleen are very rare, with all reported cases located in the pancreas . No intraabdominal cyst derived from the accessory spleen in the greater omentum, similar to our case, has been reported in the literature.…”
Section: Discussionsupporting
confidence: 69%
“…Although the histogenesis of splenic epithelial cysts is controversial, there are two main hypotheses: one is embryonic inclusion of epithelial cells from adjacent structures, and the other is invagination of capsular surface mesothelium. Recently, several cases of epithelial splenic cysts associated with high serum concentrations of CA19‐9 have been reported 1,2,10. CA19‐9 is known to be present in normal epithelial cells, such as ductal cells of the salivary glands, biliary epithelium, pancreatic ductal epithelium, and metaplastic mesothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…All types of splenic cysts are rare [3]. In a review of 42,327 autopsies, splenic cysts were found to have an incidence of 0.07% [8]. All the same, even after trauma, posttraumatic splenic cysts are rarely seen [9].…”
Section: Discussionmentioning
confidence: 99%
“…From 1978 less than 1,000 cases of true splenic cysts [21]and, more recently, less than 20 cases with elevated CA 19-9 serum levels have been reported [6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. CA 19-9 is produced by both normal and tumoural human epithelial cells; by immunohistochemical analysis, the epithelium lining a true splenic cyst may be demonstrated to produce this cancer antigen, its production depending on the degree of proliferation of the epithelium and the capsule thickness and the presence of capillaries in the connective tissue surrounding the cyst [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, its usefulness is rather limited, since elevated serum levels of CA 19-9 may be encountered in patients with benign disorders with a sensitivity of 77% and a specificity of 88% [4, 5]. Moreover, elevated basal CA 19-9 serum levels have also been described in patients with splenic cysts [6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. This is not surprising, since CA 19-9 is commonly produced by normal human epithelial cells from organs such as pancreas, salivary glands, colon, bronchial glands, endometrium, and biliary tract [16]; moreover, it has been suggested that the epithelium lining splenic cysts may produce this antigen [12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%